Strong temporal consistency in the individual foraging behaviour of Imperial Shags Phalacrocorax atriceps. (14th May 2014) - Harris, Sabrina; Raya Rey, Andrea; Zavalaga, Carlos; Quintana, Flavio; Wanless, Ross
<x xml:space="preserve">Abstract</x> Individual consistency in foraging behaviour can generate behavioural variability within populations and may, ultimately, lead to species diversification. However, individual‐based long‐term behavioural studies are particularly scarce in seabird species. Between 2008 and 2011, breeding Imperial Shags Phalacrocorax atriceps at the Punta León colony, Argentina, were tracked with GPS devices to evaluate behavioural consistency during their foraging trips. Within a breeding season, individuals were highly consistent in the maximum distances they reached from the shore and the colony, as well as in the time invested in flight and diving across consecutive days during early chick rearing. In addition, each individual had its specific foraging area distinct from the foraging area of other individuals. Comparing between early and late chick rearing in the same season, individuals were consistent, to a lesser degree, in the maximum distance they reached from the colony and the shore, increasing in consistency later on in the season. Within the season, females were more consistent than males in the maximum distance they moved from the colony and the shore, the sexes segregated in their foraging areas and individual females were segregated from one another. Twenty‐eight individuals tracked in different breeding seasons were marginally consistent in their trip durations and maximum distance reached from shore across seasons. Among seasons, foraging locations differed between sexes and among individual females. Individuals from this colony exhibited consistency over time in several aspects of foraging behaviour, which may be due to a combination of individual characteristics such as learning abilities, breeding experience or health, as well as targeted prey type and stability of the environment at this location.